Information operations, rivalry projects in the information arena - Cristinel-Marius AMZA (Bulletin of "Carol I" National Defense University)
The organization and conduct of intelligence operations in the Intelligence Arena involves a real rivalry and confrontation among the Intelligence Services, conducted in order to gain some advantages at the expense of others. Nothing is surprising in the fact that these rivals are constantly trying on the one hand to thwart each other’s efforts to know the other, and, on the other hand, to mislead, misinform, or deceive.